Evaluación numérica del rendimiento térmico de ciclos de refrigeración por absorción empleando tres mezclas de trabajo (NH3-H2O, LiBr-H2O, NH3-NaSCN). (2022)
A simulation of an absorption refrigeration cycle was carried out using simple and double effect cycles (only simple for the case of NH3 balance of the LiBrH2O, NH3H2O, NH3-- NaSCN), where the liquidvapor NaSCN mixtures was measured, for given temperatura ranges and concentrations of mass fractions, a base problems was used in a greenhouse and with this power to obtain specific data when using the solar collectors. Using the new values of the thermodynamic results o properties measured by ourselves and the btanied are compared with some bibliographic sources in order to have concrete results and make our own comparison. The experimental data were correlated by polynomial equations in order to simulate the in the engineering equation solver (EES). Th software e purpose of the project was to make a comparison of results between the mixtures to find out wich of these had the best performance and power, since the experimental one was proposed by us, the results obtained were positive since they remained in the ran ges of power, caloric requrement, among others.